Evaluadores del Volumen 35(1) (RUNA, archivo para las ciencias del hombre, 2014)
Evaluadores ExtranjerosRodrigo Diaz Cruz, Universidad Autónoma Metropolitana-Iztapalapa - UAM-Izt, MéxicoGuillermo Ruben, Universdade Estadual de Campinas -UNICAMP, BrasilSilvana Darré, FLACSO, UruguayFernanda Bittencourt Ribeiro, Pontificia Universidade Catolica do Rio Grando do Sul - PUCRS, BrasilDenise Jardim, Universidade Federal do Rio Grande do Sul - UFRGS, BrasilJeffrey Erbig, University of North Carolina at Chapel Hill, EEUUOscar Chamosa, The University of Georgia, EEUUMarco Curatola Petrocch, Ponitificia Universidad Católica del Perú – PUCP, PerúCristobal Aljovin de Losada, Universidad Nacional Mayor de San Marcos - UNMSM, PerúEvaluadores NacionalesMaría A. Soto, Instituto Universitario Nacional de Arte - IUNAAlexander Roig, Universidad Nacional de San Martín -UNSaMBrigida Baesa, Universidad Nacional de la Patagonia San Juan Bosco – UNPSJBNidia Arces, Universidad Nacional de Rosario - UNRRodolfo Cruz, Universidad Nacional de Catamarca - UNCaSilvia Ratto, Universidad Nacional de Quilmes - UNQFlorencia Roulet, Universidad de Buenos Aires - UBAGuillermina Espósito, Universidad Nacional de Córdoba - UNCWalter Delrio, Universidad Nacional de Río Negro – UNRN